Merencanakan Strategi Dan Metode Dalam Pembelajaran - Betris Susi Yanti Simbolon; Dorlan Naibaho (Jurnal Magistra, 2024)
This article digs deep to discuss the critical ability of educators in determining effective learning strategies and methods. The strategy in a lesson for students must be appropriate, we need an approach to students so that we can know each student's characteristics, so that we are easy to determine the methods and strategies that are suitable for students in learning activities. With a focus on the interaction between learning methods and learner development, this article details practical guidelines for improving the efficiency of the learning process in an ever-changing era of education so that learners get optimal learning outcomes and planned learning objectives can be achieved.